Critical thinking as a bridge between reading, reflection, and academic writing: a mixed-methods study of international doctoral candidates - Li, Su; Noordin, Nooreen; Yang, Tiantian (SAGE Publications, 2026)
This study examined the interplay between extensive reading, metacognitive experiences, and academic literacy development among international doctoral candidates, with a particular focus on the mediating role of critical thinking. Employing a sequential explanatory mixed-methods design, the research first analyzed quantitative data through Partial Least Squares Structural Equation Modeling (PLS-SEM) and subsequently enriched interpretation through qualitative semi-structured interviews. Quantitative findings demonstrated that critical thinking statistically mediates the association between reading, metacognition, and academic writing performance, highlighting the pivotal role of higher-order reasoning in doctoral literacy development. Qualitative insights further revealed that critical engagement with academic texts and reflective self-regulation strategies were crucial in transforming reading input into coherent, original scholarly writing. Together, these results advance the understanding of academic writing not as an isolated linguistic output, but as a dynamic, self-regulated cognitive and metacognitive process. The study underscores the need for doctoral programs to integrate critical reading practices, metacognitive strategy instruction, and writing support frameworks rooted in cognitive development theories. Future studies should aim to validate and refine this model across varied disciplinary and cultural contexts, and to trace the longitudinal evolution of critical thinking and writing competencies over the course of doctoral education.